Cross reactivity of spike glycoprotein induced antibody against Delta and Omicron variants before and after third SARS-CoV-2 vaccine dose in healthy and immunocompromised individuals. Issue 4 (April 2022) - Faustini, Sian; Shields, Adrian; Banham, Gemma; Wall, Nadezhda; Al-Taei, Saly; Tanner, Chloe; Ahmed, Zahra; Efstathiou, Elena; Townsend, Neal; Goodall, Margaret; Plant, Tim; Perez-Toledo, Marisol; et al.
Highlights: IgG anti-SARS-CoV-2 Omicron spike glycoprotein antibodies were detected in 100% of health care workers, a real world population attending general practice for vaccination and haemodialysis patients 4 weeks after a third SARS-CoV-2 vaccine dose (Pfizer-BioNtech 162b2). Against both Delta and Omicron variants, antibody levels were higher in the cohort who had previously received two doses of Astrazeneca ChAdOx1 nCoV-19 vaccine than two doses of Pfizer-Biontech 162b2. Prior to this third vaccine dose and 6 months post second vaccine dose, there was evidence of significant waning of antibody reactivity against Delta and Omicron variants of concern, particularly in individuals initially receiving two doses of Astrazeneca ChAdOx1 nCoV-19.